Managing the economic sustainability of the Belt and Road Initiative by applying Pragmatic Identity Matching PrIM - Markus Erbach (Journal of Innovation and Entrepreneurship, 2021)
Achieving and managing economic sustainability is one of the crucial tasks for our globalized world. One of the most ambitious economic projects known to humankind claims to stand for long-term global economic sustainability including ecological, social, and cultural aspects: the Belt and Road Initiative (BRI), in which China invites the world to join its vision of a "peaceful cooperation for the wealth and cultural exchange of all nations" (Xi Jinping 2013 in his famous speech Promote People-to-People Friendship an Create a Better Future). This invitation led to a wide range of responses, from fundamental rejection to supportive participation. Matching the participants in this megaproject-their contributions, particular prerequisites, and development interests-requires a holistic participative planning approach with solutions tailored specifically to the participating partners. This article shows how Pragmatic Identity Matching (PrIM), a scalable integration framework, can be used to meet this requirement. PrIM provides an identity-oriented infrastructure for aligned planning, implementation and communications, acknowledging, and embracing participants from different cultural backgrounds such as Asian, Arabian, African, Russian, and European cultures. As a structural-scientific approach that synthesizes elemental semiotic thinking and research in psychology and the neurosciences, PrIM provides a meta-planning structure beyond any value-driven positions and perspectives, one that imparts equivalence to information. PrIM can help the BRI avoid a spiral of non-coordinated activities, thereby preventing loss of investment. The formation of a transdisciplinary BRI Management Academy that uses PrIM would help create the necessary infrastructure for a successful and transparent implementation of the BRI.
Keywords: 650; Belt and Road Initiative; Communication model; Economic sustainability; Global governance; Intercultural communication; Knowledge transfer; Multi-stakeholder integration; Peirce; Targeted open innovation